(untitled) (Journal of Environmental Science and Natural Resources, 2013)
At present environmental education is emerging across the globe although this is a quite new phenomenon in Bangladesh. The present study was attempted to know about the environmental education and awareness among the mass people of Tangail town. In order to conduct this research, a questionnaire survey was carried out and interview was undertaken among 100 respondents in Tangail District. This paper describes some findings to understand the status of environmental awareness among people of different age groups of Tangail district. Moreover, this paper enables to provide some suggestions to extend environmental education and awareness to make a decent and ethical life as well as to keep the environment sustainable. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14828 J. Environ. Sci. & Natural Resources, 5(2): 263-266 2012